Acceptance of Technology in Online Learning Perspective at Educational Institutions : A Systematic Literature Review - Agus Pamuji (ITEJ (Information Technology Engineering Journals), 2020)
Today, many applications or technologies have been produced by every software developer. However, the success of all there is the decision of each user. Users have two possibilities to accept or reject a technology that is presented. The TAM model has been widely researched and undergone development and changes besides being quite reliable in predicting the level of technology acceptance in all countries in the world. In this study, we will recapitulate all studies on the acceptance of technology in the field of Education that handles online learning. The results showed that there was 51 article review publication were selected through some process of review. The period taken ranges from 2011 to 2020. The main findings show that there are differences in the models, methods, and applications identified. Since the TAM model has two basic variables, namely perceived ease of use and perceived usefulness as a framework for analyzing the make and influence technology acceptance. In this study also provides information about the results of the identification of some of the gaps in current research and also in the future. Therefore, the results of a systematic literature review were able to provide a better understanding of TAM especially in the perspective of education in online learning.